Pesan Dakwah dalam Iklan Deterjen dan Pewangi “Cosentrat Sahaja” - Royhaa Natul Firdaus (UNISBA Press, 2022)
Abstract.This study aims to determine the message of da'wah contained in the detergent and fragrance advertisement